Development of low-cost titanium alloys: A chronicle of challenges and opportunities - Bodunrin, Michael O.; Chown, Lesley H.; Omotoyinbo, Joseph A. (Materials today : proceedings, 2021)
The production of titanium alloys became fully commercialized in the 1950s and that was precisely 145 years since titanium ores, ilmenite and rutile were first discovered. In the 2000s, up to 100 titanium alloys of different grades were already designed, but only 20% of these alloys are in use on a commercial scale. Despite this, there is growing interest in the design of new titanium alloys owing to the global demand for stronger, lighter and less-expensive alloys for engineering applications. This paper presents an overview of the different design strategies that were adopted in producing low-cost titanium alloys since the alloys already met two important demands, strength and lightweight. Some of the challenges and opportunities that are associated with these strategies are mentioned.